The Role of Digital Education in Narrowing the Gender Digital Divide in Vietnam - Duong Van Thanh (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This paper introduces some perspectives on digital education in Vietnam and also highlights the important role of local people participating in the fourth industrial revolution. The digital revolution has emerged, expanded rapidly, and is making enormous changes in government, the economy, and social life globally and also in Vietnam. An independent survey of 1,229 students in eight universities was undertaken in April and May of the 2021 in five different regions/areas of Vietnam. This research study introduces several core elements of students’ awareness with regards to digital education in relation to face-to-face education in Vietnam during the current period. This paper addresses the current models of online education that have been applied before and during the pandemic. It focuses on analyzing the advantages and disadvantages of digital education in relation to face-to-face education among regions, particularly between urban and rural areas. Combining quantitative and qualitative research methods, the study also considers gender differences in digital education and the research results show that there is no big digital gender divide in access, use, and motivation between female and male students. Recommendations for policy makers and educators are made to further improve a systematic and strong digital education for higher education institutions in Vietnam. Received 24th August 2021; Revised 2nd January 2022; Accepted 20th March 2021